THE ROLE OF EMOTIONAL INTELLIGENCE AND SELF-EFFICACY ON THE CAREER READINESS OF MILLENNIAL STUDENTS - widiarma, In’am; ., Tegowati (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
This research aims to analyze the influence of self-efficacy and emotional intelligence on the career readiness of millennial students in Surabaya. The sample was 30 which was determined using accidental sampling technique. The data analysis technique uses SPSS 27. The research results show that self-efficacy and emotional intelligence have a significant positive effect on the career readiness of millennial students. Students who believe in their abilities adapt more easily to new work environments. They tend to feel more ready to adapt to organizational culture and job demands, so they are ready for a career. Students who have high emotional intelligence tend to be better at managing their emotions, both in pressure situations and when facing challenges at work. This can help them stay calm and think clearly, which is important in solving problems.